EMPLOYEE VOICE SCALE: IS THERE A NEED OF RECONSIDERATION OF DIMENSIONS? - Ulaş Çakar; Samina Begum (İşletme Bilimi Dergisi)
Aim: This study critically reviews the employee voice literature and demonstrate the shift of voice arrangement from employee-oriented to organizational-oriented.Methods: The previous researches and theories concerning management and employee voice were examined, and a conceptual framework of different phases of the flow of employee voice in an organization was developed. The scales adapted to measure employee voice since 1983 to 2015 were scrutinized.Findings: The finding shows that the scales used in literature are fundamentally measuring the Traditional Employee Voice (TEV), which lacks the ability to cover the overall dimensions of the Modern Employee Voice (MEV).Results: The result shows that the TEV is one-way communication process while the MEV is two-way communication process. The effect of this result on future studies was evaluated.